When Elderly Outperform Young Adults—Integration in Vision Revealed by the Visual Mismatch Negativity - Gaál, Zsófia Anna; Bodnár, Flóra; Czigler, István (Frontiers in Aging Neuroscience, 2017)
We studied the possibility of age-related differences of visual integration at an automatic and at a task-related level. Data of 15 young (21.9±1.8 years) and 15 older (66.6±3.5 years) women were analyzed in our experiment. Automatic processing was investigated in a passive oddball paradigm, and the visual mismatch negativity (vMMN) of event-related brain potentials was measured. Letters and pseudo-letters were presented either as single characters, or the characters were presented successively in two fragments. In case of simultaneous presentation of the two fragments (whole character) vMMN emerged in both age groups. However, in successive presentation vMMN was elicited only by the deviant pseudo-letters, and only in the older group. The longest stimulus onset asynchrony (SOA) in this group was 50 ms, indicating longer information persistence in elderly. In a psychophysical experiment the task was to indicate, which member of a character pair was a legal letter. Again, the letters and pseudo-letters were presented as fragments. We obtained successful integration at 30 ms (0 ms interstimulus interval), but not at longer SOAs in both age groups, showing that in case of task-relevant stimulation level there was no detectable age-related performance difference. We interpreted the results as the efficiency of local inhibitory circuits is compromised in elderly, leading to longer stimulus persistence, and hence better visual perception in this particular case.